2018
DOI: 10.3390/molecules23071705
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Principles and Other Chemical Constituents from the Mycelium of Phellinus linteus

Shiow-Chyn Huang,
Pei-Wen Wang,
Ping-Chung Kuo
et al.

Abstract: In the dimethylnitrosamine (DMN)-induced hepatic fibrosis Wistar rat model, the mycelium extract of Phellinus linteus (PLE) (20 mg/Kg) displayed significant protection against hepatic fibrosis. The present investigation characterized eleven new ionone derivatives, phellinulins D–N (4–14), from the P. linteus mycelium extract and the relative stereochemical structures were constructed according to the spectroscopic and spectrometric analytical results. Some purified compounds were examined for their inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
(59 reference statements)
0
15
0
1
Order By: Relevance
“…Terpenoids are also the major bioactive constituents of the mycelium of P. linteus and are important secondary metabolites. To date, phytochemists have discovered 13 kinds of terpenoids from the mycelium of P. linteus with pharmacological activity [29,30,40,69]. It was reported that phellilane L ( 16 ), phellidene E ( 17 ), and (−)- trans -γ-monocyclofarnesol ( 18 ) exhibited antimicrobial activities against P. gingivalis [29,30].…”
Section: Bioactive Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Terpenoids are also the major bioactive constituents of the mycelium of P. linteus and are important secondary metabolites. To date, phytochemists have discovered 13 kinds of terpenoids from the mycelium of P. linteus with pharmacological activity [29,30,40,69]. It was reported that phellilane L ( 16 ), phellidene E ( 17 ), and (−)- trans -γ-monocyclofarnesol ( 18 ) exhibited antimicrobial activities against P. gingivalis [29,30].…”
Section: Bioactive Componentsmentioning
confidence: 99%
“…In addition, atractylenolide I ( 19 ) was revealed to have antitumor activity [40]. Furthermore, phellinulin D ( 20 ), phellinulin E ( 21 ), phellinulin F ( 22 ), phellinulin G ( 23 ), phellinulin H ( 24 ), phellinulin I ( 25 ), phellinulin K ( 26 ), phellinulin M ( 27 ), and phellinulin N ( 28 ) isolated from the mycelium of P. linteus were indicated to have a hepatoprotective effect [69]. Furthermore, the chemical structure of terpenoid components is clearly correlated with pharmaceutical activities, and this relationship will be the subject of increasing research attention in the future.…”
Section: Bioactive Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The various components including polyphenols, pyrans, polysaccharides, and triterpenoids play a significant role in improving the health condition [ 23 , 24 ]. Above all, Phellinus linteus mycelium (PLM) was used as medicines or healthy foods to treat several diseases such as infections, ulcer, cancer, and diabetes [ 25 ]. In the previous reports, PLM showed wide spectrum of bioactivities, such as antioxidant, anti-inflammatory, cytotoxic, antiviral, and antidiabetic effects [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phellinus linteus is a well-known medicinal mushroom that is widely used in Korea, Japan, China, and other Asian countries [ 5 ]. In several experimental models, it has been reported that Phellinus linteus extract contains various phenolic compounds that exert various biological effects, including anti-inflammatory [ 6 , 7 ], anti-cancer [ 8 , 9 ], hepatoprotective [ 10 , 11 ], anti-diabetic [ 12 , 13 ], and neuroprotective [ 14 , 15 ] effects. Recently, it has been shown that Phellinus linteus exhibited anti-angiogenic activity in mice [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%